2011
DOI: 10.1007/s10840-011-9571-3
|View full text |Cite
|
Sign up to set email alerts
|

Utility of virtual unipolar electrogram morphologies to detect transverse conduction block and turnaround points of typical atrial flutter

Abstract: BackgroundNoncontact mapping is useful for the diagnosis of various arrhythmias. Virtual unipolar electrogram morphologies (VUEM) of the conduction block and the turnaround points, however, are not well defined. We compared the VUEM characteristics of a transverse conduction block in the posterior right atrium (RA) with those of contact bipolar electrograms obtained during typical atrial flutter (AFL).MethodsContact bipolar electrograms were used to map the posterior RA during typical AFL in 16 patients. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Fukuzawa et al ., 17 however, observed the upper turnover portion of the reentry circuit in AFL at the posterior SVC in a majority of AFL patients using a CARTO mapping system. Findings of some other previous studies support this notion 10,18,19 . In this study, only 4 of 33 AFL showed a complete block line (block proportion 100%) in the posterior RA during AFL.…”
Section: Previous Studiessupporting
confidence: 86%
See 4 more Smart Citations
“…Fukuzawa et al ., 17 however, observed the upper turnover portion of the reentry circuit in AFL at the posterior SVC in a majority of AFL patients using a CARTO mapping system. Findings of some other previous studies support this notion 10,18,19 . In this study, only 4 of 33 AFL showed a complete block line (block proportion 100%) in the posterior RA during AFL.…”
Section: Previous Studiessupporting
confidence: 86%
“…We did not record contact bipolar mapping to identify the block line in the posterior RA. Previously, however, we reported the relationship between the virtual unipolar morphologies and contact bipolar morphologies at the conduction block during typical AFL 10 . In 12 of 40 patients, a sustained AFL was not induced at the time of the electrophysiologic study.…”
Section: Limitationsmentioning
confidence: 87%
See 3 more Smart Citations